THE EVOLUTIVE SIGNIFICANCE OF POLLEN USE AS PROTEIN RESOURCE BY TRIGONINI BEES (HYMENOPTERA, APIDAE, MELIPONINAE) - Dacruzlandim, C.; Doserrao, J. E. (Assn Advan Zoology, 1994)
The origin of bees was marked by the change from the use of animal of vegetal protein to feed the larvae. The advantages of this change and the existence of some necrophagous species among the bees is discussed regarding to the poor digestibility of pollen.